Revertant mosaicism in a human skin fragility disorder results from slipped mispairing and mitotic recombination - Kiritsi, Dimitra (American Society for Clinical Investigation, 2012)
Spontaneous gene repair, also called revertant mosaicism, has been documented in several genetic disorders involving organs that undergo self-regeneration, including the skin. Genetic reversion may occur through different mechanisms, and in a single individual, the mutation can be repaired in various ways. Here we describe a disseminated pattern of revertant mosaicism observed in 6 patients with Kindler syndrome (KS), a genodermatosis caused by loss of kindlin-1 (encoded by FERMT1) and clinically characterized by patchy skin pigmentation and atrophy. All patients presented duplication mutations (c.456dupA and c.676dupC) in FERMT1, and slipped mispairing in direct nucleotide repeats was identified as the reversion mechanism in all investigated revertant skin spots. The sequence around the mutations demonstrated high propensity to mutations, favoring both microinsertions and microdeletions. Additionally, in some revertant patches, mitotic recombination generated areas with homozygous normal keratinocytes. Restoration of kindlin-1 expression led to clinically and structurally normal skin. Since loss of kindlin-1 severely impairs keratinocyte proliferation, we predict that revertant cells have a selective advantage that allows their clonal expansion and, consequently, the improvement of the skin condition.